2020
DOI: 10.3889/oamjms.2020.4605
|View full text |Cite
|
Sign up to set email alerts
|

Improved Knowledge, Attitudes, and Practices of Balanced Nutrition after Educational Intervention Based on the Self-determination Theory: An Intervention Study in Senior School Teachers in Makassar City

Abstract: BACKGROUND: Studies linking the association of nutrition knowledge, attitudes, and practices (KAP) with healthy behavior have been well established. However, the method to effectively deliver nutrition education to a particular population, especially middle-income population, was less studied. AIM: This study aimed to examine the effects of school-based nutrition using the self-determination theory (SDT) on nutrition KAP of the senior secondary schoolteacher with metabolic syndrome risk. ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…The results of this study indicate that there is no significant increase in participants' knowledge. This result is in contrast to several studies that have shown a significant improvement in the educational intervention group (Jafar et al 2020;Khaw, Ebora-Calbayan, and Pondi 2021;Mazloomy-Mahmoodabad et al 2017). Nevertheless, most of the assessments of each respondent's knowledge items were considered as "good" after being given the intervention (Table 3).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The results of this study indicate that there is no significant increase in participants' knowledge. This result is in contrast to several studies that have shown a significant improvement in the educational intervention group (Jafar et al 2020;Khaw, Ebora-Calbayan, and Pondi 2021;Mazloomy-Mahmoodabad et al 2017). Nevertheless, most of the assessments of each respondent's knowledge items were considered as "good" after being given the intervention (Table 3).…”
Section: Discussioncontrasting
confidence: 95%
“…If the results are analyzed specifically per item, none of them showed a significant increase in the post-test scores in both domains. A study by (Jafar et al 2020) demonstrated opposite findings with a significant positive result from providing educational interventions to the practices of respondents.…”
Section: Discussionmentioning
confidence: 93%
“…Nutrition knowledge was measured across 33 papers (Additional file 7 ), with 15 using the construct term ‘ Nutrition knowledge ’ with various FN-focused questions observed, including local dietary guideline recommendations ( n = 8) [ 63 , 71 , 101 – 106 ], nutrient content and/or functions ( n = 7) [ 56 , 63 , 71 , 77 , 104 , 105 , 107 ], diet-disease relationship ( n = 4) [ 63 , 104 , 106 , 108 ], food safety and/or hygiene ( n = 5) [ 71 , 77 , 106 – 108 ]. Seventeen additional papers included nutrition knowledge under different construct terms or scores including nutrition literacy [ 109 ], knowledge of nutrition score and a knowledge of nutrients functions score [ 66 ], healthy food choices knowledge score [ 110 ], or combined in a multi-faceted construct that included nutrition knowledge along with attitudes and practices questions [ 111 ]. Where constructs were identified separately as knowledge or attitudes they have been allocated to each specific thematic category.…”
Section: Resultsmentioning
confidence: 99%
“…and the second example was, "What was the composition of balanced nutrition?" [34], [35]. Subjects with scores >60 were categorized as having good knowledge [36].…”
Section: Methodsmentioning
confidence: 99%